Para-aortic lymph node surgical staging in locally-advanced cervical cancer: comparison between robotic versus conventional laparoscopy. Issue 4 (19th February 2020) - Loverix, Liselore; Salihi, Rawand Rokan; Van Nieuwenhuysen, Els; Concin, Nicole; Han, Sileny; van Gorp, Toon; Vergote, Ignace
Abstract : Objective: With the expansion of the use of minimally invasive surgical techniques within the field of gynecological oncology, a robot assisted procedure seems to be an attractive technique for para-aortic lymph node sampling. The aim of this study was to compare robotic versus conventional laparoscopic para-aortic lymphadenectomy in patients with locally advanced cervical cancer. Methods: In this monocentric retrospective study, we included patients with locally-advanced cervical cancer (International Federation of Gynecology and Obstetrics (FIGO) 2009 stage IB2-IVA or IB1 with suspicious pelvic lymph nodes), who underwent a para-aortic lymphadenectomy up to the inferior mesenteric artery between December 1994 and December 2016 (robotic technique starting from December 2012). Results: A total of 217 patients were included in the study (robotic, n=55 vs laparoscopic, n=162). When comparing conventional laparoscopic versus robotic para-aortic lymphadenectomy, the median age was 48 versus 49 years and the median body mass index was 24.4 vs 24.7 kg/m 2, respectively. In the robotic or laparoscopic group, 85% and 83% were squamous carcinomas, respectively. Patients who underwent a robotic procedure had a higher American Society of Anesthesiologists (ASA) score (ASA2: 62% vs 56%, ASA3: 20% vs 2%, p<0.001), more prior major abdominal surgery (18% vs 6%, p=0.016), less estimated blood loss (median, 25 mL vs 62.5 mL, p<0.001), more para-aortic lymph nodes removed (11 vs 6, p<0.001), shorter postoperative stay (1.8 vs 2.3 days, p=0.002), and a higher, but non-significant, rate of metastatic para-aortic lymph nodes (13% vs 5%, p=0.065) compared with the laparoscopic procedure, respectively. There was no difference in complication rates between the two approaches. The most frequent complications were grade I and grade II according to the Clavien Dindo classification. No difference was observed in progression-free survival between robotic and laparoscopic para-aortic lymphadenectomy after 2 years (both groups 66%) (p=0.472). Also, 2 year overall survival was similar between the groups (77% vs 81% for robotic vs conventional laparoscopy group, respectively) (p=0.749). Conclusion: Robotic para-aortic lymphadenectomy in patients with locally-advanced cervical cancer resulted in better perioperative outcomes and similar survival outcomes when compared with a conventional laparoscopic approach.